Edukasi Penggunaan BLU BCA Account For Teens: Literasi Keuangan Digital Untuk Pelajar Remaja - Sintia Soniantari, Luh (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2025)
The development of digital technology has driven changes in the financial system, including banking services that are now accessible to teenagers. One innovation in digital financial literacy is the use of BLU BCA Digital for Teens, which allows teenagers to learn to manage their finances independently. This KKN program was implemented at SDN 2 Sanur Kaja with the aim of providing education to 6th grade students about the importance of digital financial literacy and how to use BLU BCA Digital wisely. The method used in this activity is interactive education, which involves delivering materials, demonstrating the use of the BLU BCA Digital application, discussion, question and answer session. The result of the activity showed that students were highly enthusiastic in understanding the concept of digital banking and money management. With an interesting and age-appropriate approach, this education succeeded in increasing students’ understanding of BLU BCA features, such as creating digital accounts, recording transactions, and online transaction security. In addition, the role of teachers and parents also plays a role in supporting student’ understanding of the concept of digital financial literacy. This education proves that early digital financial literacy is very important for forming good financial habits, so that students are better prepared to manage their finances in the future.